KUALITAS PELAYANAN PUBLIK DALAM MEMENUHI KEPUASAN MASYARAKAT DI KANTOR IMIGRASI KELAS I KHUSUS SURABAYA - Rahardian, Rachman; Zakariya, Zakariya (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Quality Of Public Service in Fulfilling Community Satisfaction in Class Of Immigration Class I Special Surabaya. Public services in accordance with Act No. 25 of 2009 on the public service is a form of services either in the form of public goods, one form of public service held by the government is meeting the needs of society in the manufacture of passports by the Immigration Office. However, in the provision of services performed, there are problems that often occur like, there is always a long queue, inadequate parking space. Special Class I Immigration Office Surabaya is one of the facilities that serve service traveling abroad. The focus of research at the Immigration Service Quality Class I Special Surabaya measured using the five dimensions of service quality (SERVQUAL) According to Parasuraman, namely Tangible, Realibility, Responsiveness, Assurance, Empathy. This study used a qualitative descriptive approach. Results from the study show that: 1) The services in Class I Special Immigration Office of Surabaya in society already said enough good can be seen from the Tangible, Realibility, Responsiveness, Assurance, Empathy. 2) Conditions of service given Class I Special Immigration Office Surabaya to communities based on Tangible, Realibility, Responsiveness, Assurance, Empathy has been said to be quite good. 3) community satisfaction with the services in Class I Special Immigration Office Surabaya already be quite good, which includes Realibility, Assurance, Empathy. But the satisfaction of the people are still not satisfied because there are said to be found lacking from the dimension Tangible, Responsiveness. 1) The services in Class I Special Immigration Office of Surabaya in society already said enough good can be seen from the Tangible, Realibility, Responsiveness, Assurance, Empathy. 2) Conditions of service given Class I Special Immigration Office Surabaya to communities based on Tangible, Realibility, Responsiveness, Assurance, Empathy has been said to be quite good. 3) community satisfaction with the services in Class I Special Immigration Office Surabaya already be quite good, which includes Realibility, Assurance, Empathy. But the satisfaction of the people are still not satisfied because there are said to be found lacking from the dimension Tangible, Responsiveness. Â Keywords: Quality of Public Services, Public Satisfaction